Opportunity cost of the exporting commercial agricultural sector in Peru, 1998-2017 - Magallanes Díaz, Juan F. (2021)
The objective of the investigation was to determine the opportunity cost in the commercial export agricultural sector, based on in the economic foundations for Peru, period 1998-2017. The methodology of the research was explanatory and was carried out under a longitudinal non-experimental design, with the application of the capital asset price model (CAPM) for determining the opportunity cost of the exporting commercial agricultural sector of Peru, in the period 1998-2017. Data were processed from the share price indices of 19 agricultural companies listed on the Lima Stock Exchange. The results showed the relationship of market performance variables and systematic risk (Beta) in the determination of the opportunity cost of the commercial agricultural exporting sector, obtaining a value greater than 29%. In conclusion, there is viability of agricultural projects and businesses that previously were not because much higher rates were applied, managed by the banking system in Peru.